Management of breakthrough pain due to cancer - Hilgier, Maciej (Contemporary Oncology/Współczesna Onkologia, 2001)
Breakthrough pain is defined as the transient exacerbation of pain occuring in a patient with otherwise stable, persistent pain. Breakthrough pain is relatively common among cancer patients (affects over 50% of patients), particularly those with moderate to severe background pain. Breakthrough pain is one of the most difficult pain syndromes to treat. There is a number of types of breakthrough cancer pain. Incident: flares of pain associated with movement or activity. Idiopathic: transitory pain unrelated to the last dose of around-the clock medication or to a specific activity, and end-of-dose failure: pain occuring when blood levels of medications fall below an analgesic threshold at the end of a dosing interval. Persistent and breakthrough pain are distinct components of cancer pain is treated with a supplemental short-acting opioid used "as needed" (oral transmucosal fentanyl being the most interesting). Increasing the dose of around-the clock medication to cover all episodes of breakthrough pain is one of the option, but often leads to over-sedation. One must consider also paracetamol and NSAID's as rescue medication. Athough breakthrough pain is usually managed with supplemental analgesics medication, other means of treatment should be considered such as primary antineoplstic therapies, orthotic devices, neural blocks and thermolesions etc.